The Effect of Reminiscence Therapy Using Virtual Reality on Apathy in Residential Aged Care: Multisite Nonrandomized Controlled Trial - Dimitrios Saredakis; Hannah AD Keage; Megan Corlis; Erica S Ghezzi; Helen Loffler; Tobias Loetscher (JMIR Publications, 2021)
BackgroundApathy is a frequent and underrecognized neurological disorder symptom. Reduced goal-directed behavior caused by apathy is associated with poor outcomes for older adults in residential aged care. Recommended nonpharmacological treatments include person-centered therapy using information and communication technology. Virtual reality (VR) in the form of head-mounted displays (HMDs) is a fully immersive technology that provides access to a wide range of freely available content. The use of VR as a therapy tool has demonstrated promise in the treatment of posttraumatic stress disorder and anxiety. In addition, VR has been used to improve conditions including depression, anxiety, cognitive function, and balance in older adults with memory deficits, Alzheimer disease, and Parkinson disease. Research using VR for the symptoms of apathy in older adults living in residential aged care facilities is limited. ObjectiveThis study aims to examine whether using HMDs as a tool for reminiscence therapy improves the symptoms of apathy compared with using a laptop computer and physical items with older adults living in residential aged care. MethodsIn this multisite trial, 43 participants were allocated to one of three groups: reminiscence therapy intervention using VR in the form of HMDs, reminiscence therapy using a laptop computer supplemented by physical items if required (active control), and a usual care (passive control) group. The primary outcome was apathy, and the secondary outcomes included cognition and depression. The side effects of using HMDs were also measured in the VR group. ResultsMixed model analyses revealed no significant group interaction over time in outcomes between the VR and laptop groups (estimate=−2.24, SE 1.89; t40=−1.18; P=.24). Pooled apathy scores in the two intervention groups compared with the passive control group also revealed no significant group interaction over time (estimate=−0.26, SE 1.66; t40=−0.16; P=.88). There were no significant secondary outcomes. Most participants in the VR group stated that they would prefer to watch content in VR than on a flat screen (Χ22=11.2; P=.004), side effects from HMD use were negligible to minimal according to the Simulator Sickness Questionnaire cutoff scores. ConclusionsAlthough there were no significant results in outcome measures, this study found that participants engaged in the research and enjoyed the process of reminiscing using both forms of technology. It was found that VR can be implemented in an aged care setting with correct protocols in place. Providing residents in aged care with a choice of technology may assist in increasing participation in activities. We cannot dismiss the importance of immediate effects while the therapy was in progress, and this is an avenue for future research. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12619001510134; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=378564. International Registered Report Identifier (IRRID)RR2-10.1136/bmjopen-2020-046030